PENGARUH METODE PEMBELAJARAN KOLABORATIF TERHADAP KETERAMPILAN SOSIAL PADA ANAK TUNARUNGU KELAS IV DI SKH GYHTA KYARA 02 KABUPATEN PANDEGLANG BANTEN - Moch. Aldy Ghifary; Dr. Joko Yuwono, M.Pd; Sistriadini Alamsyah Sidik, M.Pd (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2018)
This study aims to determine the effect of collaborative learning methods on social skills in deaf children in total SDLB classes in Skh Gytha kyara 02. The approach used in this study is a research approach in the form of Single Subject Research (SSR). The design used is A-B-A. The research subject was a deaf child in total class IV SDLB who had a condition that was passive in interacting. From the data obtained then analyzed through descriptive statistical analysis and displayed in the form of polygon tables and graphs. The components analyzed include analysis in conditions and analysis between conditions. Based on the results of the research conducted, there was an increase in the frequency of social skills especially in aspects of familiar behavior and empathy in the subject. The target frequency of the behavior that the subject raised in the baseline condition (A-1) has four sessions with frequencies 3, 4, 3. 3, and. At the time of intervention (B) there were eight sessions with a frequency of 6,7,7,8,9,8,10,10. While at baseline-2 (A-2) there werpe four sessions with a frequency of 8,9,9,9. Based on the data obtained, the use of collaborative learning methods on social skills especially on aspects of familiar behavior and empathy on the subject is indicated by the increased frequency of social skills on intervention and baseline-2 and supported by low overlap. The results of the baseline-I inter-condition analysis with the overlap percentage intervention were 0% and increased in the inter-condition analysis of the intervention with baseline-II at 25%. Overall the application of collaborative learning methods has a positive and effective effect used to improve social skills in 4th grade deaf students at the Gytha  Kyara 02 Carita